The Effects Of Early And Delayed Palatal Repair On Maxillary Growth And Speech Outcome In Unilateral Cleft Lip And Palate Patients: A Systematic Review - Raden Ratu Kania Tiaraningrum; Made Surya Dharmawan; Ida Ayu Cempaka Dewi Yatindra; Ratna Rayeni Natasha Rooseno (Jurnal Anestesi, 2024)
Some cleft clinics use a two-stage method to correct the cleft palate, which helps avoid reduced maximum growth after early hard palate surgery and impaired speech development after late soft palate repair.. This study sought to evaluate the effects of early vs late palatoplasty on speech and maximum growth results. The following databases were searched: Cochrane Library, Science Direct, Pubmed, and NCBI. The primary objective of this study was to determine whether unilateral, non-syndromic cleft lip, alveolus, and palate patients who underwent early or late hard palate surgery before or after 18 months of age had an impact on speech and maxillary development. Things like case studies, reviews, editorials, textbooks, and studies conducted on animals weren't included. The following systematic observations consist of eight studies. Most studies had methodological quality that ranged from fair to good. This review discusses the experience of cleft centers using a variety of one and two stage palatoplasty procedures and timing, and shows inconsistent results regarding maximal progression. The seemingly inconsistent results of the studies included in this observation of speech outcomes suggest that there is insufficient evidence to conclude whether one- or two-stage palatoplasty has a significant effect on maximal development for a variety of reasons. The review provides inconclusive evidence on the impact of hard palate repair timing on facial growth and speech outcomes in unilateral cleft lip and palate patients, highlighting the need for further controlled studies.